2019
DOI: 10.1021/acsmedchemlett.9b00141
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Pyrazolocarboxamides as Potent and Selective Receptor Interacting Protein 2 (RIP2) Kinase Inhibitors

Abstract: Herein we report the discovery of pyrazolocarboxamides as novel, potent, and kinase selective inhibitors of receptor interacting protein 2 kinase (RIP2). Fragment based screening and design principles led to the identification of the inhibitor series, and X-ray crystallography was used to inform key structural changes. Through key substitutions about the N1 and C5 N positions on the pyrazole ring significant kinase selectivity and potency were achieved. Bridged bicyclic pyrazolocarboxamide 11 represents a sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…This work is the first to demonstrate the efficacy and modulatory activity of a RIP2-targeting compound using a clinically relevant model of allergic asthma. Numerous inhibitors have both been discovered and developed for modulation of RIP2 activity (23,(41)(42)(43)(44)(45)(46)(47)(48)(49). The RIP2 inhibitor used in this study, GSK583, has been reported to be highly selective and exhibits strong potency even in vivo (23,45).…”
Section: Discussionmentioning
confidence: 99%
“…This work is the first to demonstrate the efficacy and modulatory activity of a RIP2-targeting compound using a clinically relevant model of allergic asthma. Numerous inhibitors have both been discovered and developed for modulation of RIP2 activity (23,(41)(42)(43)(44)(45)(46)(47)(48)(49). The RIP2 inhibitor used in this study, GSK583, has been reported to be highly selective and exhibits strong potency even in vivo (23,45).…”
Section: Discussionmentioning
confidence: 99%
“…This work is the first to demonstrate the efficacy and modulatory activity of a RIP2 targeting compound using a clinically relevant model of allergic asthma. Numerous inhibitors have both been discovered and developed for modulation of RIP2 activity (23,(35)(36)(37)(38)(39)(40)(41)(42)(43). The RIP2 inhibitor utilized in this study, GSK583, has been reported to be highly selective and exhibits strong potency even in vivo (23,39).…”
Section: Discussionmentioning
confidence: 99%
“…In the following compounds, the 1,3‐diazepine scaffold was not a crucial element of the structure and could be replaced by smaller rings without affecting their potency. In Figure 23 are reported compounds stimulating AMPK 170 and modulating ɣ‐secretase 171 activities, as well as inhibitors of human β‐secretase (BACE1), 172,173 polymerase bacteriophage T7 ARN, 174,175 Factor Xa, 176 RIP2, 177 phosphatidylcholine‐preferring phospholipase C, 178 acetylcholinesterase, 179,180 and squalene synthase 181 …”
Section: 3‐diazepine Derivatives As Enzyme Inhibitorsmentioning
confidence: 99%